2004
DOI: 10.1128/ec.3.4.900-909.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of URA3 Can Influence the Virulence Phenotypes and Proteome of Candida albicans but Can Be Overcome by Targeted Reintegration of URA3 at the RPS10 Locus

Abstract: Uridine auxotrophy, based on disruption of both URA3 alleles in diploid Candida albicans strain SC5314, has been widely used to select gene deletion mutants created in this fungus by "Ura-blasting" and PCR-mediated disruption. We compared wild-type URA3 expression with levels in mutant strains where URA3 was positioned either within deleted genes or at the highly expressed RPS10 locus. URA3 expression levels differed significantly and correlated with the specific activity of Ura3p, orotidine 5-monophosphate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
231
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(248 citation statements)
references
References 103 publications
9
231
2
1
Order By: Relevance
“…The phenotypic deficiencies correlated with reduced OMPase activity, and the filamentation defects were bypassed by uridine supplementation (Cheng et al, 2003). Similar results were obtained by Brand et al (2004), who further showed that integration of URA3 at the RPS10 locus allowed for normal expression.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The phenotypic deficiencies correlated with reduced OMPase activity, and the filamentation defects were bypassed by uridine supplementation (Cheng et al, 2003). Similar results were obtained by Brand et al (2004), who further showed that integration of URA3 at the RPS10 locus allowed for normal expression.…”
Section: Introductionsupporting
confidence: 73%
“…Similarly Brand et al (2004) demonstrated reduced URA3 expression in a number of mutants and restoration of normal expression with integration of the marker at the RPS10 locus. Again, the poorly expressed marker was within the context of flanked hisG repeats, which were not included at the RPS10 locus (Brand et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1A). The URA3 gene was reintegrated at the neutral RPS1 locus to avoid ectopic URA3 expression problems (Brand et al 2004), creating the mutant GCY 214. The GRX2 gene and URA3 were integrated at the RPS1 locus of the Δ sod1/ grx2 null mutant to generate the Δ sod1/grx2 + GRX2 reintegrant (GCY 215) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Gene disruption was confirmed by polymerase chain reaction (PCR). To avoid potential problems associated with ectopic expression of URA3 (Brand et al 2004), the Ura-Δsod1/grx2 mutant was transformed with StuI-digested CIp10 plasmid (Murad et al 2000), thus ensuring URA3 expression at the neutral RPS1 locus (orf19.3002).…”
Section: Methodsmentioning
confidence: 99%
“…5A); therefore, the mutant strain exhibited delayed lethality. The location of the URA3 gene in XC414 (DRG1 + complemented strain) differed from its location in XC101 (WT), and may have influenced the virulence of the complemented strain, as observed previously (Brand et al, 2004;Lay et al, 1998).…”
Section: Myc-tagged Drg1p Was Primarily Localized In the Cytoplasmmentioning
confidence: 60%